Pengaruh Kualitas Pelayanan terhadap Loyalitas Nasabah Tabungan BSM - Aziz, Ervin Kumala (Iqtishodia: Jurnal Ekonomi Syariah, 2017)
This research tries to reveal about the quality of service and its effect on customer loyalty of product tabungan BSM in Bank Syariah Mandiri KC. XXX Malang city. In this study used a quantitative approach to the type of explanatory research and conducted through surveys. The samples used were 100 respondents, using simple random sampling technique, using service quality dimension including compliance, reliability, responsiveness, assurance, empathy, and tangibles as an independent variable and customer loyalty of product tabungan BSM as an independent variable. Data analysis using IKP (Index of Service Quality) as well as simple linear regression processed with the help of Microsoft Excel and SPSS 21. The results of this study, seen from the level of service quality indicate that the quality of service at Bank Syariah Mandiri KC. XXX Malang city is satisfactory. This is indicated by the mount IKP of all dimensions with an average of IKP of 4,05 if converted to 81.00. The results of simple linear regression analysis on R square show that 37.6% of service quality variables an able to endowment or contribute to customer loyalty of product tabungan BSM, and the remaining 62,4% is explained by other reasons beyond the variables studied in this study. Simple linear regression test shows loyalty service, which means if all independent variables are worth (0) then the value of -4,629, if the value of service quality increases 1% then customer loyalty up 25,4% and vice versa. While the hypothesis test, through T test and F test shows the quality of service influence on customer loyalty product tabungan BSM KC. XXX Malang city, with t-count 7,683>t-table 1,98, and f-count 59,035>f-table 3,94. Keyword: Quality of Service, Customer Loyalty, Tabungan BSM